Formulation of Sorghum-Based High-Protein Crackers Enriched with Wheat and Soybean Flours for Toddlers: Formulation of Sorghum-Based High-Protein Crackers Enriched with Wheat and Soybean Flours for Toddlers - Mananda, Afan Bagus; Wardhana, Danu Indra; Setiawan, Andika Putra; Aulia, Anisa Nurina; Syafia, Fina (Universitas Darussalam Gontor, 2025)
Various complementary food menus have been distributed to help parents who are confused about choosing their child's first food menu. The complementary food menu is usually made from rice flour which is a source of carbohydrates. The high consumption of rice currently encourages various food diversification efforts to avoid dependence on one commodity. Crackers that combine sorghum flour with soybean flour increase the protein content of crackers so that they can be an alternative nutritious complementary food for stunted toddlers. The purpose of the study was to determine the effect of high-protein cracker formulation with the addition of sorghum and soybean flour and the analysis of water, ash, fat, protein and carbohydrate content. The experimental design used was a Completely Randomized Design (CRD) and a sample of five samples with two repetitions. Data analysis used the One-Way Anova test and Duncan's further test with a significance level of 0.05. The results showed that all formulas had significant differences based on the One-Way Anova test and had met the standard (SNI) for cracker quality which can be seen from the significance value. The best formulation with chemical test results is F3 with a protein content of 7.66%, fat content of 9.55%, ash content of 1.52%, water content of 3.7%, and carbohydrate content of 77.7%. Crackers products that combine sorghum flour with soybean flour increase the protein content of biscuits so that they can be an alternative nutritious complementary food for toddlers. Keywords: sorghum flour, soybean flour, crackers, food additives